Immunofluorescent Localization of Plakoglobin Is Altered in Endomyocardial Biopsy Samples from Dogs with Clinically Relevant Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) - Eva M. Oxford (MDPI AG, 2021)
Diagnosing the early stages of canine Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is complicated by day-to-day arrhythmia variability, and absence of reliable, transthoracic echocardiographic features. Definitive diagnosis requires histopathologic identification of transmural fibrofatty replacement of the right ventricle. Reduction of immunofluorescent signal for plakoglobin (PG) at the intercalated disc (ID) is reported in ARVC-affected humans and boxers. Our objective was to determine whether reduced immunofluorescent signal for PG in endomyocardial biopsy samples (EMBs) correspond with a histopathologic diagnosis of ARVC. Here, 49 dogs were evaluated: 43 with advanced cardiac disease and 6 non-clinical boxers with mild to moderate ventricular arrhythmia (VA) burden. EMBs were obtained from all dogs; samples were prepared with antibodies recognizing cadherin (PC) and PG and evaluated with confocal microscopy. Investigators were blinded to breed and clinical status. ARVC was histopathologically diagnosed in 8 out of 49 dogs. Of these, three out of eight had clinical signs consistent with ARVC (two boxers, one English bulldog) and reduced PG signal at ID; five out of eight were non-clinical boxers with moderate VA and no reduction in PG. A total of 41 out of 49 dogs were histopathologically diagnosed with non-ARVC cardiac disease; 1 out of 41 showed reduction of PG at ID, while 40 out of 41 had no PG reduction. These results suggest that EMB PG signal is reduced in dogs with advanced ARVC, but not in the occult phase of the disease. Additionally, presence of PG at ID supports a diagnosis of non-ARVC cardiac disease in dogs with clinical signs. These results may offer an additional test that helps differentiate advanced ARVC from other myocardial diseases.